Standardization of leaf extract of red betel(Piper crocatum) leaves using ethanol - Heni Sundari; M. Hatta Prabowo; Farida Juliantina Rachmawaty; Hady Anshory Tamhid (Faculty of Medicine, Universitas Islam Indonesia, 2015)
Background: Red betel vine (Piper crocatum Ruiz & Pav) is known empirically to have properties to cure various kinds of diseases. It contains flavonoids, alkaloids, polifenolat compounds, tannins and essential oil compounds. Standardization in the pharmacy is required to ensure the level of quality, fulfill the standard requirement of chemical, biological, and pharmaceutical, including the guarantee of stability as pharmaceutical products generally.Objective: To investigate the standard specific and non-specific parameters set by Food and Drug Supervisory Agency (FDSA) of ethanol leaf extract of red betel leaves.Methods: The study began with sample preparation, then extracted by maceration method to get the active compounds in the lumpy extract. Extract was analyzed with standard specific and non-specific parameters set by FDSA. Results were analyzed with descriptive analysis method.Results: The features of leaf extract of red betel vine leaves using are organolepticly viscous, dark green,and has a distinctive odor with a bitter spicy taste. The yield, water content, ash content, and specific gravity of extract were 14.8%, 0.353%, 0.16%, 0.729 respectively. Total mold contamination of extract satisfied the standard criteria that was below the limit of a maximum of 10 colonies/gram. Metal contamination of lead (Pb) was 1. 404 mg/kg and Cadmium (Cd) was 0. 223 mg/kg. Chromatographic profile of the Gas Chromatography-Mass Spectrometry (GC-MS) red betel vine leaves ethanol extract contains compounds caryophyllene, germacrene-D and some other compounds with low similiaritas index, and has a marker compound which is suspected possibly trimethoxyallyl benzen.Conclusion : The ethanol extract of red betel vine (Piper crocatum Ruiz & Pav) leaves is an extract of the organolepticly viscous, dark green color, distinctive smell, bitter taste, and spicy. The ethanol extract of red betel vine leaves satisfies the standard level set by FDSA and has the marker compound which is expected likely Trimethoxyallyl benzen.